HPTLC assay of nicotine and cotinine in biological samples - Ana Maria Vlasceanu; Daniela Luiza Baconi; Anne Marie Ciobanu; Vlad D. Constantin; Liana Pleș; Cristian Balalau; Miriana Stan (Journal of Mind and Medical Sciences)
This study presents the development of a simple high-performance thin layer chromatography (HPTLC) method for the determination of nicotine and its metabolite cotinine in human plasma and urine. The following mobile phases: methanol: ammonia (100:1.5, v:v), chloroform: acetone: ammonia (48.75: 48.75: 2.5, v:v:v), methanol: chloroform: ammonia (48.75: 48.75: 0.5, v:v:v) and glass plates precoated with silicagel 60 F254 (20x20) as a stationary phase were used. Densitometric scanning was performed at 263 nm. Two different extraction procedures have been applied: liquid-liquid extraction using dichloromethane at alkaline pH and solid-phase extraction using C18 cartridges. Preliminary tests in order to establish the system of solvents for development, as well as the range of linearity, were conducted. The best separation of nicotine and cotinine was obtained by using methanol: chloroform: ammonia (48.75: 48.75: 0.5, v:v:v) as the mobile phase. The liquid-liquid extraction technique led to better results than solid phase extraction. The regression curves were linear (with a corresponding correlation coefficient higher than 0.99) in the quantities range of 200 ng–1000 ng/spot for both nicotine and cotinine. The UV spectra confirm the identification of nicotine and cotinine both in the standards and in the extracts after liquid-liquid extraction. The proposed method can be applied for the simultaneous evaluation of nicotine and cotinine in biological samples at toxic/lethal levels. Thus, the method may be applicable in lethal nicotine intoxication cases in forensic toxicological analysis.